In vitro activity of azthreonam, a monobactam antibiotic. - Jacobus, N V (1982)
We studied the activity of azthreonam (SQ 26,776), a novel monocyclic beta-lactam compound, against a variety of clinical isolates. It was more potent than moxalactam, cefoperazone, cefamandole, cefoxitin, ticarcillin, tobramycin, or amikacin against strains of Klebsiella spp., Serratia spp., and the Proteus group. It was highly effective against Escherichia coli and strains of Salmonella spp. The median minimal inhibitory concentration for all species of Enterobacteriaceae was less than or equal to 2 micrograms/ml. Azthreonam was moderately active against Pseudomonas aeruginosa, including tobramycin-resistant strains, and against Pseudomonas cepacia (median minimal inhibitory concentration, 16 to 32 micrograms/ml), but was weakly active against Pseudomonas maltophilia and strains of Acinetobacter spp. and Achromobacter spp. The drug showed little activity against Staphylococcus aureus, enterococci, and anaerobic bacteria, including Bacteroides fragilis, Clostridium spp., and gram-positive cocci. Like moxalactam and cefoperazone, azthreonam exhibited a considerable inoculum effect with strains of Enterobacter spp. and Pseudomonas spp. Combination with clavulanic acid did not increase the activity of azthreonam against S. aureus but was synergistic for 5 of 15 strains of B. fragilis. Azthreonam is about 50% bound to human serum protein. The selective range of activity of this compound could be of clinical benefit.